The benefits of physical activity and the environment on university students’ mental health - Sonja Kaldalóns Þórhallsdóttir 1996- (2020)
Physical activity practices and its beneficial effect on mental health have been widely researched. Studies have demonstrated that a moderate amount of physical activity can help reduce symptoms of anxiety and increase well-being. However, there is a lack of research on the interplay between physical activity and the physical and social environment in which the practices takes place, with anxiety and well-being as an outcome measure. This was the objective of the current study. A total of 133 students, both males (n=42) and females (n=91) from the University of Reykjavík, participated in this study. Information was gathered on background, physical activity levels, sedentary behaviour, physical activity environment and companionship. Anxiety and well-being was assessed. Analysis revealed that students had good mental health. Those who engaged in moderate physical activity according to, or more than the official recommendations, did not fare better in terms of anxiety or mental well-being than those who did less or no physical activity. No significant differences were found in the participants’ anxiety and mental well-being in relation to indoor or outdoor environments. Having company during physical activity outdoors affected participants’ mental well-being (p < .05). Key words: mental well-being, anxiety, physical activity, environment, companionship Hreyfing og jákvæð áhrif hennar á andlega heilsu og líðan eru vinsæl rannsóknarefni. Niðurstöður sýna að hófleg hreyfing getur dregið úr kvíðaeinkennum og bætt andlega líðan. Hins vegar er skortur á rannsóknum sem kanna hvort æfingaumhverfi eða félagsskapur á meðan á æfingum stendur skipti máli í andlegum ávinningi hreyfingar. Þetta var meginmarkmið rannsóknarinnar. Þátttakendur voru 133 talsins, bæði karlar (n=42) og konur (n=91) sem stunda nám í Háskólanum í Reykjavík. Aflað var upplýsinga um bakgrunn þátttakenda, lengd og tíðni hreyfingar,kyrrsetu, æfingaumhverfi og félagsskap á meðan á hreyfingu stendur. Kvíði og andleg líðan þátttakenda var metin. Helstu ...